PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOUR, PSYCHOLOGICAL CAPITAL DAN WORK ENGAGEMENT TERHADAP TURNOVER INTENTION (Studi pada Karyawan PT Bank Mandiri KCP Pandanaran) - Adi, Hanif Prasetya; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT In the current era, many companies are paying close attention to employee turnover rates, as high turnover can have detrimental effects on a company. Maintaining employee retention is a vital strategy that can significantly impact a company's quality. In addition to striving for employee retention, companies must also pay attention to the workload they face. This study employed a quantitative method with a cross-sectional study design. The population and sample in this research comprised 70 employees of PT Bank Mandiri KCP Pandanaran, selected using saturation sampling technique. Data collection was conducted through a census method utilizing a questionnaire as the data collection tool. This research aims to analyze the impact of are Organizational Citizenship Behaviour, Psychological Capital, and Work Engagement on Turnover Intention in PT Bank Mandiri KCP Pandanaran. The research results show that higher Organizational Citizenship Behaviour will result in lower Turnover Intention. Psychological Capital also has an influence in reducing Turnover Intention. Work Engagement does not have an impact on the level of Turnover Intention. PT Bank Mandiri KCP Pandanaran can Maintaining good relationships with employees is a crucial step in creating a sense of ownership and loyalty towards the company. This can be achieved by recognizing employee contributions, strengthening relationships, fostering a positive work environment, and providing additional support such as improving workplace facilities and enhancing security. When employees feel valued and fully supported, they are more likely to provide more positive and responsive feedback. As a result, employees will feel more comfortable in their roles and will not consider leaving the company